Impact of Collagenated and Non-Collagenated Deproteinized Bovine Bone Mineral on Schneiderian Membrane Integrity in Rabbits - Rihito Yamada; Samuel Porfirio Xavier; Yasushi Nakajima; Erick Ricardo Silva; Daniele Botticelli; Yuki Teranishi; Shunsuke Baba (Dentistry Journal)
Background: This investigation focused on the influence of collagen on the integrity of the Schneiderian membrane during maxillary sinus augmentation in a rabbit model. The aim of this study was to elucidate the relationship between membrane integrity and bone regeneration in augmented maxillary sinuses using collagenated and non-collagenated grafts, through detailed histological and histomorphometric analyses. Methods: In this forward-looking, randomized, split-mouth design, bilateral maxillary sinus augmentation was conducted on 12 rabbits. One sinus was filled with deproteinized bovine bone material (DBBM) as the grafting material (non-collagenated; control), while a combination of DBBM particles integrated with 10% porcine-derived type I collagen was used in the contralateral sinus (collagenated; test). Histological analyses were carried out following healing periods of 2 and 12 weeks. Results: At the 2-week time point, six sites of thinned mucosa (<40 µm) and no perforations were observed in the collagenated group, while twenty-one thinned mucosa sites (p = 0.027 between test and control) and two perforations (p = 0.175 between test and control) were found in the non-collagenated group. After 12 weeks of healing, the number of sites with thinned mucosa was 20 in the collagenated group and 19 in the non-collagenated group, with four perforations observed in each group. These perforations were distributed across three sinuses in the collagenated group and two sinuses in the non-collagenated group. No statistically significant differences were found between the groups. Conclusions: The addition of 10% collagen to deproteinized bovine bone mineral initially provided protection against mucosal thinning and perforation after 2 weeks of healing. However, by week 12, this protective effect diminished, resulting in similar rates of mucosal thinning and perforations in both groups.